(untitled) (Asian Journal of Ethnobiology, 2023)
Abstract. Gobana AH, Telila H, Jilo SA. 2023. Short Communication: Ethnobotanical study of medicinal plants used to treat livestock ailments in Dallo Manna District, Oromia State, Ethiopia. Asian J Ethnobiol 6: 127-136. Historical information on the use of medicinal plants is in danger of extinction due to changes in different parts of the world, including Ethiopia. This study aimed at the ethnobotanical analysis of medicinal plants used to treat animal diseases. Data were collected through semi-structured interviews with the selected informant sources. Analysis of ethnobotanical data used the Informant Consensus Factor (ICF), preference ranking, ranking matrix, and calculating the degree of fidelity. Dallo Manna Region was reported to have all 68 medicinal plant species used to treat veterinary diseases. The most common family is Fabaceae (7 spp.), followed by Euphorbiaceae (5 spp.), Asteraceae (5 spp.), and Solanaceae (4 spp.). The local people generally used the root, followed by leaves, seeds, and stems, to prepare drugs for treating livestock diseases. All medicine is made and used immediately; some are boiled and dried. In addition, the most common route of administration for treating animal diseases in the study area is oral, followed by topical application and nasal. The highest consensus criteria (ICF) values were recorded in ophthalmology, followed by dermatology. Most species have been reported for treating gastrointestinal disorders, followed by species for treating skin diseases and fever. Ten participants compared nine herbs used to treat veterinary diseases to determine their rankings. Hagenia abyssinica (Bruce) J.F.Gmel. in the first place, then this was followed by Zingiber officinale Roscoe and Embelia schimperi Vatke in third place, which achieved the highest value among traditional medicinal plants. The main threats to veterinary medicinal plants are overharvesting of available species, agricultural land expansion, and less attention to traditional medicine due to modernization.